Nature of C-(A)-S-H Phases Formed in the Reaction Bentonite/Portlandite. (18th December 2014) - Fernández, Raúl; González, Lorena; Ruiz, Ana Isabel; Cuevas, Jaime
Abstract : Reactions between bentonite/montmorillonite and portlandite have been studied in the context of the engineered barriers of a purpose built repository for the deep geological disposal of spent fuel and high-level radioactive wastes. Portlandite was selected as the representative material of cement leaching in the early alkaline stage expected in a repository when conventional Ordinary Portland Cement (OPC) is used. Eight different batch experiments were performed for a reaction time near to two months, including bentonite or montmorillonite at montmorillonite/portlandite molar ratios of 2 : 1 and 3 : 1 under hydrothermal conditions. Temperatures of reactions were maintained constant at either 60 or 120°C. Calcium silicates hydrates with limited substitution of Al for Si (C-(A)-S-H phases with Al/Si <0.3) were formed with different structures and compositions as a function of the reaction conditions. Orthorhombic 11 Å-tobermorite-type phase was detected in experiments at 120°C while a more disordered monoclinic tobermorite formed at 60°C. These results are useful for the interpretation of experimental data in more complex experiments using concrete or cement pastes and bentonite, where C-(A)-S-H phases of variable compositions can precipitate, in addition to the characteristic cement hydrates and other secondary minerals carbonates.